Redeploying Technologies ICT for Greater Agency and Capacity for Political Engagement in the Kelabit Highlands - Poline, Bala (MIT Press, 2014)
The chapter examines why and how the Kelabit, a people of Central Borneo, engaged with information and communication technologies through the electronic Bario (e-Bario) development initiative. It explores the ways that aspects of Kelabit society and history provided the context for implementation of the project, and constituted a rationale for attitudes to social change among the Kelabit. The chapter argues that the basis for adoption and application of ICT in the Kelabit Highlands was framed by local understandings of ‘progress’ and ‘development’, and conditioned by fundamental Kelabit concepts of doo-ness, or ‘goodness’, and iyuk, or status mobility. Through doo-ness and iyuk the kelabit engaged with new tropes of success and progress associated with the e-Bario initiative as a development project. The Kelabit used ICT to facilitate greater political agency and capacity for engagement with government, to preserve their cultural identity and protect traditional land rights. The hegemonic imperatives of new forms of technology were subordinated to and integrated with existing practices and values, sociopolitical arrangements and products in the Kelabit community. The Kelabit case thus illustrates the ways in which engagement and appropriation of developmental initiatives can subvert the intended outcomes of policy makers with regard to the use of ICTs as drivers of development.